Ten years later. Issue 3 (1st December 2020) - Morlino, Leonardo
Abstract : A decade ago, Regions & Cohesion started with an editorial article by Harlan Koff and Carmen Maganda, who proposed launching "a multilingual (English, French, and Spanish) and interdisciplinary forum for the discussion of the human and environmental impacts of regional integration as well as governance processes."